Impact of Tooth Surface Loss on the Quality of Life of Patients Seen in a Nigerian Teaching Hospital (2020)
Background: Tooth surface loss (TSL) is a progressive process arising from erosion, abrasion, attrition or abfraction. It can affect individuals of any age group: children, young adult, adults or the elderly and can compromise the health of individual tooth or the entire dentition leading to poor quality of life of the affected person. Objective: To evaluate the pattern of TSL among dental patients in a Nigerian Teaching Hospital and to assess the impact of TSL on their quality of life. Subjects and Methods: The study was a cross-sectional study among patients with TSL in a Nigerian Teaching Hospital. The Oral Health Impact Profile-14 (OHIP-14) questionnaire was used to obtain information on the impact of TSL on the quality of life of the participants. Data collected were analysed using IBM SPSS version 20. Chi-square test was used to assess association between types of TSL and quality of life of the patients. Level of significance was set at p ≤ 0.05. Results: One hundred and twenty-five patients (Males = 72; Females = 53) with tooth wear lesions participated in the study. The most common type of tooth surface loss was attrition (40%) followed by abrasion (23.2%). The highest impact of TSL on the quality of life was painful sensation strongly affecting 39 (31.2%) patients. This was followed by problem with chewing. There was no statistically significant relationship between patients’ quality of life and types of tooth surface loss. Conclusion: The most common negative impact of TSL on patient quality of life was painful sensation.